Determinants Analysis of Nutritional Status of Pregnant Women in the Stunting Locus Area of North Middle East District - Renty Alfany Zena Senduk; Intje Picauly; Enjelita M. Ndoen (Lontar : Journal of Community Health, 2022)
The nutritional status of pregnant women greatly affects the growth of the fetus is conceived. Pregnant women will give birth to a healthy baby at full term with a normal weight if they have good nutritional status before and during pregnancy. However, the nutritional status of pregnant women in the North Middle East District stunting locus is still not good. This study aimed to determine the effects of income levels, education levels, consumption patterns of pregnant women, and personal hygiene on the nutritional status of pregnant women in the North Middle East Regency stunting locus. This type of research is a quantitative study using a cross-sectional design. The sample consists of 45 pregnant women with a total sampling technique. The data analysis was performed using univariate and bivariate analysis with the chi-square test. The results showed that factors moreover influenced the nutritional status of pregnant women were the consumption pattern of pregnant women (p-value= 0,015), and personal hygiene (p-value= 0,023), while the factors that did not affect were income level (p-value= 0,931) and education level (p-value= 0,365). Lastly, pregnant women are expected to pay more attention to nutritional status and consumption patterns by consuming balanced nutritious foods and maintaining personal hygiene during pregnancy to prevent the occurrence of malnutrition status in mother's pregnancy.